Democracy and freedom from the point of view of karls poper (Raparin Journal of Humanities (RJH), 2024)
This study deals with the philosophy of freedom and democracy by Karl Popper. Popper discusses the causes of the emergence of establishing a government from the perspective of democracy and freedom of elections. The main issue of the study is whether the emergence of government depends of man’s ability, and freedom and security of society. Popper believes that all the individuals are equal in front of the law because the legal states do not differentiate among the individuals who are equal in origin, language, culture, and gender. The state should also defend the land and control the military and economic sources. The democracy which is a political system depending on using rationality in politics or any other field needs an open society as political parties are tools for establishing governments. Popper believes that the wider the freedom is, it will be better for the government. Popper talks about democracy that no government is established without freedom and democracy. A dictator is a person who can be a president and calls for democracy and freedom of expression, but he rejects the other types of democracy because democracy has been known for rejecting dictatorship. In noocracy system, authority is given to a person, not for all, thus a president isn’t selected. To achieve secure and stable society, the government uses two types of elections, they are in the society and in the parliament. However, parliamentary elections are the most important ones topple the dictatorship without blood shedding.